Situation Report: Hungary, 26 May 1970 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Fock on the 24th Comecon Session Press Criticizes Inequalities between Large and Small Enterprises National Conference on "Cultural Propagation among the Peoples" Summer University Courses in Hungary, 1970 Acceleration of the Pork Program The Cost of Agricultural Modernization - 120,000 Million Forint The State Farm System: A Brief Profile